Cara Pandang Guru Kristen Terhadap Siswa Sebagai Gambar dan Rupa Allah yang Membutuhkan Pemuridan - Parinding, Lorita; Tangkin, Wiyun Philipus (Sekolah Tinggi Teologi Kanaan Nusantara, 2022)
The perspective that is owned by the teacher will affect his actions towards students. That is why teachers must have the right perspective so they can educate students well. Christian teachers should have the perspective that students are the image of God who has fallen into sin so students need the process of restoring the image of God.However, the phenomenon that occurs today in the world of education is the existence of acts of violence committed by teachers as a form of education given to students. Seeing this phenomenon, then this study was written to find out how Christian teachers should see the students so that Christian teachers can carry out their roles properly in school. The conclusion obtained is that Christian teachers must see students as the image of God but have fallen into sin. This perspective can help Christian teachers carry out their task of guiding students in the process of restoring the image of God through discipleship. The author is aware of the shortcomings in this writing, therefore the advice that can be given to the next writer is to be able to examine what steps teachers can take in discipleship for the process of restoring the image of God in students through Christian education.